2020
DOI: 10.1101/2020.05.13.20100800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic risk for Alzheimer disease, cognition and Mild Behavioral Impairment in healthy older adults

Abstract: BACKGROUND: Mild Behavioral Impairment (MBI) is a neuropsychiatric syndrome describing later-life emergent apathy, mood/anxiety symptoms, impulse dyscontrol, social inappropriateness and psychosis that are not attributable to psychiatric diagnoses. MBI is an at-risk state for incident cognitive decline and dementia, and is associated with dementia biomarkers including amyloid beta; and neurofilament light. Thus, MBI may be an early clinical marker of neurodegenerative disease. In this study, we hypothesized … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Another two studies were excluded from the meta‐analysis because their populations overlapped with those of previous studies, but they were suitable for systematic review (Table S1). 20, 21 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another two studies were excluded from the meta‐analysis because their populations overlapped with those of previous studies, but they were suitable for systematic review (Table S1). 20, 21 …”
Section: Resultsmentioning
confidence: 99%
“…With regard to the defining criteria for MBI, six studies used the Neuropsychiatric Inventory Questionnaire, three studies used the ISTAART criteria, and two studies used MBI‐C (Table 1). Thirteen studies were included in the systematic review to examine the effect of MBI in predicting cognitive deterioration, correlations to underling pathology or biomarkers, and genetic risks 20, 22–33 . No previous systematic review or meta‐analysis was identified.…”
Section: Resultsmentioning
confidence: 99%
“…Although MBI and MCI can co-occur, MBI can also precede MCI, manifesting in older adults with subjective cognitive decline or even normal cognition, in whom MBI has demonstrated an increased risk of cognitive decline and dementia [22][23][24][25][26]. MBI may be the initial manifestation of neurodegeneration for some, and has been connected with known biomarkers for dementia including amyloid beta [27], tau [28,29], neurofilament light [30], cortical atrophy [31,32], white matter atrophy [33], and AD risk genes [34,35]. MBI has also been used in machine learning models to predict neurocognitive diagnostic category 40 months later [36].…”
Section: Introductionmentioning
confidence: 99%
“…Although MBI and MCI can co-occur, MBI can also precede MCI, manifesting in older adults with subjective cognitive decline or even normal cognition, in whom MBI has demonstrated an increased risk of cognitive decline and dementia (22)(23)(24)(25)(26). MBI may be the initial manifestation of neurodegeneration for some, and has been connected with known biomarkers for dementia including amyloid beta (27), tau (28,29), neuro lament light (30), cortical atrophy (31,32), white matter atrophy (33), and AD risk genes (34,35).…”
Section: Introductionmentioning
confidence: 99%